PELAKSANAAN INOVASI LAYANAN POJOK BRAILLE (LAPO BRA) DALAM MENINGKATKAN PELAYANAN PUBLIK (Studi pada Dinas Perpustakaan Umum dan Arsip Daerah Kota Malang) - Florentina Nduet (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The Office of the Public Library and Regional Archives of Malang City in order to improve public services which launched a service called the Braille Corner Service (Lapo Bra), which is intended for blind persons with disabilities where they can enjoy the same services as the general public. The purpose of this study was to learn how to implement "Braille Corner Services" in improving public services and to find out the supporting and inhibiting factors for the implementation of "Braille Corner Services" in improving public services in the Public Library and Archives of Malang City. This study used qualitative research methods. Data sources used primary and secondary data. Data collection is done through observation, interviews, and documentation. The technique of determining informants using purposive sampling. The technique of analyzing the data collected, presentation data, and conclusions collected. "Braille Corner Service" The Office of the Public Library and Regional Archives of Malang City has helped well to support the information needs of net users and to help enjoy the same services as the general public and improve community services, this is proven by using 6 (six) standard points according to public services mahmudi 2010. With the Braille Corner Service that can improve the quality of life of blind disabilities through information technology, foster the creation of reading interests, and foster self-confidence for net disabilities.